Halal Industry Management in Islamic Economic Perspective - Fata, Zainol; Suhaimi, R.; Fany, Naufal El (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Indonesia is a country that has enormous potential in the halal industry. In 2020 spending on the halal industry reached USD 184 billion and is projected to increase by 14.96% in 2025 or reach USD 281.6 billion. To maximize the potential that is owned, good management is needed in the halal industry so that this potential can develop optimally. In this study the researchers focused on the problem of how to manage the halal industry and how the halal industry is in the perspective of the Islamic economy. This research is a qualitative research. The research method used in this research is literature review. The data collection method used is secondary data obtained from journals, documentation books, and the internet. In the research that has been carried out, it produces findings based on the focus of the research, namely the Majamenen Halal Industry has been regulated based on the Laws of the Republic of Indonesia, one of which is Number 33 of 2014 concerning Guarantees for Halal Products. While the halal industry in the perspective of Islamic economics is in accordance with Islamic economic theory and principles